Implementasi Planning Programming Budgeting System Dalam Manajemen Pembiayaan Pendidikan - Shelty Deity Meity Sumual; Suiling Pontoh; Maria Kaparang; Victor Nomel Kumajas (Journal on Education, 2024)
The importance of financing management in education is to ensure the success of educational institutions both academically and financially. A well-managed financing system helps ensure that funds are allocated efficiently and effectively, improving the quality of education and providing benefits to students and educators. Planning Programming Budgeting System is a management method used to allocate limited resources effectively in an organization. It involves goal setting, plan creation, budgeting, and progress tracking. This helps agencies to prioritize their goals and ensure that they use their resources in a responsible and effective manner. The research method used in this study is a descriptive research method, where this research establishes a qualitative approach with literature studies. The result of the research is the implementation of the Planning Programming Budgeting System (PPBS) aims to create a comprehensive, consistent, and transparent reporting framework for educational institutions. By using this system, the management of funding allocation can be accounted for through cost control, financial projections, tracking, and cost reporting. The PPBS system effectively manages education financing by ensuring the provision of reliable, transparent, and accurate financial data in a timely manner. This ultimately improves the financial stability and sustainability of the institution, as well as the quality of education for its students.